2013
DOI: 10.3109/2000656x.2012.754626
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic distal radioulnar synostosis

Abstract: Radioulnar synostosis is rare, and exists in two forms: congenital and post-traumatic. The congenital form presents only in the proximal forearm, and the post-traumatic form may present anywhere along the radius and ulna. The only known aetiology for distal radioulnar synostosis is post-traumatic. We present a rare case of distal radioulnar synostosis with no previous history of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…5 This ossification limits the development of the radius along the longitudinal axis of the forearm. 6 In the presence of a malformation, the closing of the epiphysis also may have contributed to the occurrence of the valgus deformity as well as dislocation of the radial head observed in this patient. In support of this theory, preoperative DR showed that the fusion site was at the original location of the proximal radialis epiphysis.…”
Section: Discussionmentioning
confidence: 76%
“…5 This ossification limits the development of the radius along the longitudinal axis of the forearm. 6 In the presence of a malformation, the closing of the epiphysis also may have contributed to the occurrence of the valgus deformity as well as dislocation of the radial head observed in this patient. In support of this theory, preoperative DR showed that the fusion site was at the original location of the proximal radialis epiphysis.…”
Section: Discussionmentioning
confidence: 76%
“…Врожденный радиоульнарный синостоз (ВРУС) -редкая аномалия развития верхней конечности, возникающая на ранних этапах эмбриогенеза в результате нарушения дифференцировки из общего перихондрия проксимальных отделов лучевой и локтевой костей [1]. Несмотря на то, что в литературе описан единичный клинический случай идиопатического дистального лучелоктевого синостоза [2], авторы предполагают, что этиология данного состояния отличается.…”
Section: Introductionunclassified